Estudo comparativo dos processos de separação na obtenção do biodiesel de óleo de palma bruto (Elaeis guineensis, Jacq) - RIBEIRO, Haroldo Jorge da Silva (Universidade Federal do Pará, 2017)
This work investigated the influence of the separation processes on the yield and properties relating to the quality of biodiesel from crude palm oil ( Elaeis guineensis, Jacq ) obtained in laboratory scale , such as decantation , centrifugation , evaporation , washing and dehydration, where the following operating conditions are used : the settling time ( sludge/neutral oil ) - 120 minutes at 50 ° C; settling time used for washing the neutral oil 60, 90 and 120 minutes at 50 °C; H2O percentages used in washing the neutral oil 10%, 20% and 30% ( m./m.); temperatures centrifugation for separating the neutral/oil sludge and washings neutral oil 40, 50 and 60 °C; temperature and pressure range of dehydration of neutral oil and biodiesel and 80 °C from 480,0 to 80,0 mbar respectively; temperature and pressure in the evaporation of excess ethanol 75 °C and 213,3 and 146,6 respectively March; the settling time of biodiesel/glycerol system and washes 60, 90 and 180 minutes at 50 °C; operating temperature used in the centrifuge separation system biodiesel/glycerin 50 °C; H2O percentage of biodiesel used for washing by centrifugation 20% relative to the ester phase. The results found that neutralization in general was satisfactory as generated about 10% of blurs, highlighting the Experiment 1 that generated about 84,6% by weight of neutral oil. Washes in 90 minutes (Exp. 1) and 20% water (exp.2) showed the best performance for the separation by settling, while in the process of centrifugation and washing better separation occurred at 40 and 50 ° C respectively. In relation to the evaporation of ethanol, the best percentage in alcohol was obtained at 80 °C and 1466 mbar. Regarding the separation of phases rich in glycerol esters and the process of centrifugation at 50 °C led to a better quality biodiesel, however, the best yields were observed in the biodiesel from the settling process. The final evaluation of the biodiesel produced in this study was positive, because most of the analyzed parameters is according to the official specifications.